Comparative performance of trypanotolerant and more susceptible cattle breeds exposed to trypanosomiasis in Gabon - Ordner, G.; D'Ieteren, G.D.M.; Dumont, P.; Itty, P.; Jeannin, P.; Maehl, H.M.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Thorpe, W.R.; Trail, J.C.M.; Yangari, G. (OAU/STRC, 1988)
Reports the influence of breed and animal age on the prevalence, species and intensity of trypanosome infection and the effects of the infections on the blood packed cell volume (PCV) of N'Dama, Nguni and crossbred cattle. Presents the effects of trypanosome infection, PCV level and lactational status on reproductive performance and liveweight of N'Dama cattle. Compares the mortalities of different breeds exposed to trypanosomiasis risk.